The Effectiveness of Conservation Athletic Games for Non-Formal Education Learning Primary School Age (Universitas Negeri Semarang, 2022)
Athletics is one of the elements of physical education as well as a component of overall education that prioritizes physical activity. This study aims to analyze the effectiveness of conservation athletic game products for elementary students. This research is done using a research and development approach. The development model used is the ADDIE model which includes analysis, design, development, implementation, and evaluation. The development of conservation athletic games includes: ) Lompat galah; 2) Roket; 3) Sunda manda; 4) Gapar; 5) Gayap; 6) Lompat tali; 7) Lari; 8) Zona rotasi; 9) Balap karung; 10) Lempar sasaran; 11) Gelindingan ban; 12) Estafet. The small-scale trial was given to 17 students at SDN 2 Honggosoco. A large-scale trial was conducted on 170 elementary school students in Kudus Regency. The results of this study stated that the results of physical education teachers showed the category of